Characteristics of transformational leadership and its impact on achieving entrepreneurial requirements A survey study of the opinions of a sample of administrative leaders at the Technical University of Sulaimani - Majed Mohammed Saleh; Ahmed Suleiman Mohammed Al-Jarjari; Kazem Faraj Aref (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The present study aims to present and analyze all of the transformational leadership Features basic requirements entrepreneurial as the basic pillars for achieving the contemporary organizations competitively distinct site in light of heightened competition in an environment of changes rapidly, so we chose came to these two variables in order to stand at the fact that the role of transformational leadership in achieving entrepreneurial requirements adopted at the technical University of Sulaymaniyah, Through a survey the opinions of the administrative leaders and description and diagnosis of the main study and sub-variables as well as the analysis of correlations and influence their Dependence. Questionnaire form prepared for this purpose . Reached study to a number of scientific results which established a field conclusions have been invested through the recommendations made by the Technical University of Sulaymaniyah faculties and technical institutes, colleges and similar institutions as evidence of the work to provide the best performance on the level of technical education institutions.